2018
DOI: 10.1007/s10723-018-9462-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Text Using Emotion Detected from EEG Signals

Abstract: Often people might not be able to express themselves properly on social media, like not being able to think of appropriate words representative of their emotional state. In this paper, we propose an end to end system which aims to enhance user-input sentence according to his/her current emotional state. It works by a) detecting the emotion of the user and b) enhancing the input sentence by inserting emotive words to make the sentence more representative of the emotional state of the user. The emotional state o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Hatamikia et al [ 44 ] found that spectral entropy outperformed the Petrosian and Katz fractal dimensions for emotion recognition. Gupta et al [ 35 ] used SVD entropy as part of a set of features to classify discrete emotion for short movies. Equations are as given in [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hatamikia et al [ 44 ] found that spectral entropy outperformed the Petrosian and Katz fractal dimensions for emotion recognition. Gupta et al [ 35 ] used SVD entropy as part of a set of features to classify discrete emotion for short movies. Equations are as given in [ 72 ].…”
Section: Methodsmentioning
confidence: 99%
“…Various machine learning techniques have been investigated to improve the performance of emotion recognition and other health related systems (e.g., stroke management) using EEG [ 30 , 31 ]. Many classical classifiers have been proposed, including support vector machine (SVM) [ 32 , 33 , 34 ], linear discriminant analysis (LDA) [ 33 , 34 ], k-nearest neighbours (kNN) [ 33 ], random forest (RF) [ 35 , 36 ], Naïve Bayes (NB) [ 32 , 36 ], extreme gradient boosting (XGB) [ 32 ], and decision trees [ 33 , 36 ]. The performances achieved by these classifiers vary, and differences are often overshadowed by the impact of the features chosen as part of these models.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the early ERC methods, Poria et al 13 proposed bidirectional contextual LSTM (bc-LSTM) to capture contextual information from their surroundings. Gupta et al 31 proposed a method to detect and enhance the emotion of the user on social media by analyzing the electroencephalogram signals from the brain. Hazarika et al 32 proposed a conversational memory network for dyadic dialogs utilizing speaker-specific context modeling.…”
Section: Related Workmentioning
confidence: 99%
“…Here, EEG signals are typically obtained using the international 10-20 system, which is an internationally recognized method for describing and applying the location of the scalp electrode and underlying area of the cerebral cortex [ 40 ]. Moreover, the “10” and “20” in the international 10-20 system refer to the fact that the actual distance between the adjacent electrodes is either 10% or 20% of the total left-right or front-back distance of the skull.…”
Section: Proposed Approachmentioning
confidence: 99%